Is the Relation Between the Solar Wind Dynamic Pressure and the Magnetopause Standoff Distance so Straightforward?. Issue 8 (25th April 2020) - Samsonov, A. A.; Bogdanova, Y. V.; Branduardi‐Raymont, G.; Sibeck, D. G.; Toth, G.
Abstract: We present results of global magnetohydrodynamic simulations which reconsider the relationship between the solar wind dynamic pressure ( P d ) and magnetopause standoff distance ( R SUB ). We simulate the magnetospheric response to increases in the dynamic pressure by varying separately the solar wind density or velocity for northward and southward interplanetary magnetic field (IMF). We obtain different values of the power law indices N in the relation R SUB ∼ P d − 1 / N depending on which parameter, density, or velocity, has been varied and for which IMF orientation. The changes in the standoff distance are smaller (higher N ) for a density increase for southward IMF and greater (smaller N ) for a velocity increase. An enhancement of the solar wind velocity for a southward IMF increases the magnetopause reconnection rate and Region 1 current that move the magnetopause closer to the Earth than it appears in the case of density increase for the same dynamic pressure. Plain Language Summary: The magnetopause is the boundary between the near‐Earth space, which is governed by the magnetic field produced in the Earth's core, and interplanetary space populated by the plasma emitted from the Sun called the solar wind. It is well known that the position of this boundary is defined by the balance of the pressures from both sides of the magnetopause and in a unique way depends on the velocity and density of the plasma in the interplanetary space. In this work, we reexamine the relationship between the magnetopause position and parameters of the solar wind by means of computer modeling. It is shown that the relationship between solar wind velocity and density and magnetopause position is more complex than originally thought. It is suggested that the pressure balance condition through the magnetopause depends on the continuing magnetic reconnection between the interplanetary and magnetospheric magnetic field lines and that the consequences of the reconnection change the relationship between the solar wind dynamic pressure and magnetopause boundary location. Key Points: We reconsider the relation between the solar wind dynamic pressure and magnetopause standoff distance The magnetopause reacts differently to density, and velocity increases for the same dynamic pressure A new scaling law for magnetopause standoff distance is proposed